2015
DOI: 10.4103/0971-5916.162091
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of mucosal microbiota in the colon of patients with inflammatory bowel disease revealed by real time polymerase chain reaction amplification of 16S ribosomal ribonucleic acid

Abstract: Background & objectives:Alterations in microbial communities closely associated with the intestinal mucosa are likely to be important in the pathogenesis of inflammatory bowel disease (IBD). We examined the abundance of specific microbial populations in colonic mucosa of patients with ulcerative colitis (UC), Crohn's disease (CD) and controls using reverse transcription quantitative polymerase chain reaction (RT-qPCR) amplification of 16S ribosomal ribonucleic acid (16S rRNA).Methods:RNA was extracted from col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 29 publications
7
44
3
1
Order By: Relevance
“…In contrast to the previous statements that for patients with CD decrease in Firmicutes to Bacteroidetes ratio is typical 72 , in our study, the decreased serum vitD level was associated with more favorable microbiome of the gut of IBD patients.…”
contrasting
confidence: 99%
“…In contrast to the previous statements that for patients with CD decrease in Firmicutes to Bacteroidetes ratio is typical 72 , in our study, the decreased serum vitD level was associated with more favorable microbiome of the gut of IBD patients.…”
contrasting
confidence: 99%
“…This ratio is often used as a proxy for microbial health status (40)(41)(42)(43)(44)(45) and, more specifically, to describe the degree of dysbiosis in IBD (43)(44)(45). Of note, the phylum-level population shifts from Bacteroidetes to Firmicutes induced by DSS in our study resemble those observed in obese individuals and in animals on a high-fat diet and have been associated with low-grade intestinal and systemic inflammation in obesity (46,47).…”
Section: Discussionsupporting
confidence: 62%
“…Gophna et al [11], and Bibiloni et al [12] showed a significant increase of Bacteroidetes in CD than in UC patients. However, in an Indian population, Kabeerdoss et al [13] found greater Bacteroides and Lactobacillus concentration in inflamed colonic mucosa of patients with UC in comparison to CD patients.…”
Section: Introductionmentioning
confidence: 99%